DECISION MAKING SUPPORT MODELS IN THE MANAGEMENT OF ENTERPRISES AT NETWORK STRUCTURES: SECURITY KNOWLEDGE BASE - BUIIAK, Lesia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In modern conditions one of most relevant aspects the ensuring effective functioning of enterprises at network structures, as well the formation of positive results its economic activity in the context of security science, is the implementation of decision-making in the management of the network system. A complex of mathematical methods and decision support models in the management of enterprises at network structures has been developed, which will allow to optimize the activity of network systems taking into account security guidelines. The scientific problems of the system at network enterprises include the following stages: the study of the competitive environment and the study of influencing factors; development of an approach to assessing the impact of network business competitiveness; development of a set optimization models and methods of managing enterprises at network structures. On the basis of this, it was established that the provision of economic security is the main vector the formation of approaches to the calculation of relevant economic and mathematical characteristics at network enterprises, taking into account external and internal influencing factors.
Keywords: enterprises of network structure; decision making in management; economic-mathematical model; network modulation; economic security; security vectors of development